The neoconservative theory of international politics - Larwood, Zane (AUC Knowledge Fountain, 2018)
Neoconservatism has largely not been considered a theory of international relations. In this paper, I seek to answer the following questions: Can neoconservatism be considered an international relations theory, or is it something else? If it is the former, is neoconservatism a unique theory in and of itself, or is it a variation of an already existing theory, like neorealism or neoliberalism? Given its basis in the monadic democratic peace theory and concrete views on national interests, this paper argues that neoconservatism has all the components of an ontological IR theory and therefore should be treated as such. Though similar in many ways to liberal IR theory, neoconservative IR theory is distinct because, unlike liberal theories, it is extremely skeptical of international institutions and collective state action more broadly.